Effect of oxide on surface tension of molten metal. Issue 85 (23rd November 2017) - Li, Chunkai; Shi, Yu; Gu, YuFen; Yang, Fuqian
Abstract : System for the measurement of surface tension of molten metal; variation of d〈 γ 〉/d t with coating density of oxides. Abstract : Oxides as one of the commonly activating fluxes used in active tungsten inert gas welding (A-TIG welding) can dramatically increase the penetration depth to 2–4 times that of conventional welding. Using the oscillation principle of inviscid fluid, a robust method is developed to measure the average surface tension of molten metal during A-TIG welding for four different oxide activating fluxes of B2 O3, TiO2, SiO2, and MgO. The experimental results suggest that the oxygen released from the decomposition of oxides is the dominant factor contributing to the change of the surface tension, which can result in the change of the temperature coefficient from negative to positive and alter the Marangoni convection, leading to the increase in the penetration depth. However, oxygen of small amount or large amount has a negligible effect on the sign change of the temperature coefficient. For oxides of low melting points, the interaction between the electrons outside the arc and the neutral particles (atoms and molecules) formed from the dissolution of the oxides causes the constriction of the arc; for oxides of high melting points, the decrease of the spot area in the anode due to high resistivity of the oxides leads to the constriction of the arc.